The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/pbc.26061
|View full text |Cite
|
Sign up to set email alerts
|

Late Toxicities of Intensity‐Modulated Radiation Therapy for Head and Neck Rhabdomyosarcoma

Abstract: Purpose/Objectives To examine the late effects of intensity modulated radiation therapy (IMRT) in pediatric patients with rhabdomyosarcoma of the head and neck. Materials/Methods All one-year survivors of pediatric head and neck rhabdomyosarcoma treated with IMRT at a single institution from 1999-2014 were assessed for long term complications. Late toxicities were graded according to CTCAE version 4.03. Results Among 30 patients, median age at IMRT was 7.4 (1.5-20.8) years, median follow-up was 7.7 (1.2-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 19 publications
0
77
0
3
Order By: Relevance
“…76.7% of patients had facial disfigurement, 36.7% of patients demonstrated growth hormone deficiency, 33.3% demonstrated dental problems, 20% had hearing loss, 20% had visual disturbance, and 6.7% had a secondary malignancy. 5 These rates appear to be reduced in studies of RMS patients using PBT, with 0-30% rates of decreased growth velocity, 20-70% facial hypoplasia, 0-8% visual complications, 3-30% dentition issues, 0-3% auditory complications, and no reported secondary malignancies. 11,13 If late toxicities are reduced, PBT may allow for dose escalation in refractory histologies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…76.7% of patients had facial disfigurement, 36.7% of patients demonstrated growth hormone deficiency, 33.3% demonstrated dental problems, 20% had hearing loss, 20% had visual disturbance, and 6.7% had a secondary malignancy. 5 These rates appear to be reduced in studies of RMS patients using PBT, with 0-30% rates of decreased growth velocity, 20-70% facial hypoplasia, 0-8% visual complications, 3-30% dentition issues, 0-3% auditory complications, and no reported secondary malignancies. 11,13 If late toxicities are reduced, PBT may allow for dose escalation in refractory histologies.…”
Section: Discussionmentioning
confidence: 93%
“…Late toxicities include dental anomalies, xerostomia, craniofacial abnormalities, trismus, endocrine abnormalities, cataracts, and osteoradionecrosis. [3][4][5] In addition, areas exposed to radiation are at risk for secondary malignancies that may manifest decades after primary radiation therapy. 6 Proton beam therapy (PBT), using double scattering proton therapy (DS-PT) or pencil beam scanning proton therapy (PBS-PT) techniques, has been shown in dosimetric studies of adult head and neck malignancies to reduce the amount of normal tissue exposed to radiation compared to modern photon plans.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Furthermore, other adverse events, such as growth hormone deficiency and cataract, are frequently reported. [4][5][6][7] The impact of these adverse events on psychosocial well-being is unclear. Multiple studies showed that, in general, health-related quality of life (HRQoL) in survivors of childhood cancer is comparable with normative values of healthy individuals; however, specific subgroups are at risk for impaired psychosocial wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Lockney et al described late toxicities after IMRT for 30 patients with HNRMS treated at Memorial Sloan Kettering. 38 With a median follow-up of 7.7 years, the most common late toxicity observed was facial disfigurement, seen in 77% of patients. Children treated at younger ages (median 6.0 years) and those with infratemporal fossa tumors were more likely to develop severe facial deformity.…”
Section: Late Effectsmentioning
confidence: 99%